2013
DOI: 10.1260/2041-4196.4.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Afterburning Aspects in an Internal TNT Explosion

Abstract: The afterburning is a complex chemical process which stems from the reaction of the detonation products with the oxygen in the air when appropriate conditions exist. TNT is a very fuel-rich explosive as indicated by the large negative oxygen balance value of −74%. It means that there is not enough oxygen in its initial chemical compound and extra oxygen is needed to make the afterburning energy release possible. This article describes in details the calculation process for evaluating the amount of energy relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 13 publications
4
41
0
Order By: Relevance
“…All the studied cases refer to deficiency in oxygen chambers (i.e. W/V vessel > 0.387 kg-TNT/m 3 , Table 1) and should show a final QS temperature of 2800 K in agreement with the chemical equilibrium (Edri et al, 2013). Nevertheless, it can be observed that the QS temperature that is calculated from the 3D model disagrees with those from the chemical equilibrium approach because gases are modeled by independent EOS and are not described such as a unique gas that should be modeled by a variable gamma ideal gas EOS (Edri et al, 2013;Hernandez et al, 2016).…”
Section: Temperature Effectsmentioning
confidence: 74%
See 1 more Smart Citation
“…All the studied cases refer to deficiency in oxygen chambers (i.e. W/V vessel > 0.387 kg-TNT/m 3 , Table 1) and should show a final QS temperature of 2800 K in agreement with the chemical equilibrium (Edri et al, 2013). Nevertheless, it can be observed that the QS temperature that is calculated from the 3D model disagrees with those from the chemical equilibrium approach because gases are modeled by independent EOS and are not described such as a unique gas that should be modeled by a variable gamma ideal gas EOS (Edri et al, 2013;Hernandez et al, 2016).…”
Section: Temperature Effectsmentioning
confidence: 74%
“…After the dynamic response of the chamber, a significant final temperature is observed for the FC chambers associated with the QS state. For example, the chemical equilibrium predicts that the final temperature of the gas mixture is approximately equal to T QS = 2800 K when chambers are deficient in oxygen, that is, W/V vessel > 0.387 kg-TNT/m 3 (Edri et al, 2013). This temperature is so high that ventilation seems to be mandatory, taking into account that the forging temperature for carbon steels is approximately 1500 K. Figure 12 shows the temperature time-history obtained from the 3D model associated with the FC and PC chambers.…”
Section: Temperature Effectsmentioning
confidence: 99%
“…It is quite possible caused by neglecting the afterburning effect. During the simulation in AUTODYN, the standard JWL equation (Eqn 4) takes no account of the afterburning energy due to additional combustion processes (Edri et al 2012(Edri et al , 2013. On the other hand, the subsequent reflected values of the simulation are a bit larger than those recorded in the chamber test.…”
Section: Validation Of Numerical Methodsmentioning
confidence: 99%
“…As such, preliminary testing led to a domain of 10 7 5 × × m being specified, with rigid surfaces placed on the upper and lower surfaces (ceiling and floor), and two of the four walls, see Figure 8. The two remaining boundaries were specified to be ambient so sufficient venting is provided to the domain and energy increase through afterburning (Edri et al, 2013) and quasi-static pressure development (Anderson et al, 1983) is negligible. The domain can therefore be considered as 'fully vented' according to the definition in UFC 3-340-02 (US DOD, 2008).…”
Section: Generation Of Datasetmentioning
confidence: 99%